Identificación y frecuencia de garrapatas SP en caninos de tres fundaciones animales del municipio de Popayán (2022)
During the months of February to May 2022, an investigation was carried out on the identification and frequency of Spp ticks in canines in three foundations of the municipality of Popayán; A total population (150 animals) was selected from these foundations, a sample of 30 animals was taken and individually checked for tick infestation, in addition to the count, all the ticks collected from the selected canines were taken and placed in a wide mouth bottle with 70% ethyl alcohol, the samples were transported to the laboratory of parasitology of the Antonio Nariño University for the corresponding identification and to obtain the results. Once the ticks were collected, they were analyzed and classified according to gender. In total, 79 ticks were collected from the three foundations, of which 48 were from the Animal Life Foundation, 31 from the Come Dog Foundation, while no one was found in the Animal Protection Foundation. no tick. Regarding the frequency of ticks in canines in the three foundations, an infestation was observed in the animal foundation was 66.6% (20), in the eat dog foundation 63.3% (19), while in the animal protection foundation it was 0%. In the identification it was found that the 48 ticks analyzed in the animal life foundation were 100% Riphicehalus sanguineus; Of the 39 founding dog-eating ticks, 62.5% (20) were Riphicephalus sanguineus and 34.3% (11) were Riphicephalis microplus.